Moving from intersectional hostility to intersectional solidarity: Insights from LGBTQ individuals in Turkey. Issue 3 (18th June 2019) - Kamasak, Rifat; Ozbilgin, Mustafa; Baykut, Sibel; Yavuz, Meltem
Abstract : Purpose: Treatment of intersectionality in empirical studies has predominantly engaged with individual categories of difference. The purpose of this paper is to demonstrate that there is utility in exploring intersectionality at the intersection of individual and institutional levels. As such the authors move beyond the polarised take on intersections as either individual or institutional phenomenon and tackle intersectionality as a relational phenomenon that gains meaning at the encounter of individuals and institutions in context. Therefore, the authors explicate how intersectionality features as forms of solidarity and hostility in work environments. As such the authors posit that not only individuals but also the institutions should change if inclusion is aimed at societal and organisational levels. Design/methodology/approach: A thematic analysis on qualitative interview data of a purposive- and snowball-selected sample of 11 lesbian, gay, bisexual, transgender and queer working adults in Turkey was used. Findings: This paper finds evidence to support the existence of a multidimensional model of intersectionality, where conflicting and complementary individual and institutional intersections create four intersectional typologies in the form of intersectional hostility, intersectional struggle, intersectional adjustment and intersectional solidarity. Originality/value: The extant literature offers rich insights into individual intersectionality but sheds very little light on institutional intersectionality and its interaction with individual intersectionality. This paper attempts to fill in this gap by investigating intersectional encounters as interactions between the individual and institutional intersections.